Automated Mycoplasma genitalium molecular macrolide resistance detection and nucleic acid target semi-quantitation: patient demographic considerations - Josephine Moore; Trinity Krueger; Amanda Zapp; Stephen C. Lavey; Kimber L. Munson; Irene A. Stafford; Michael E. Newcomb; Brian Mustanski; Erik Munson (Microbiology Spectrum, 2025)
ABSTRACT Recent work has optimized parameters of a real-time reverse transcriptase PCR-based laboratory-developed test on the Panther Fusion system which detects Mycoplasma genitalium-specific macrolide resistance-associated mutations LDT (MRM-LDT) from primary swab and urine specimens. In this study, MRM-LDT was applied to a large multi-demographic study set to further characterize M. genitalium resistance in the United States. A total of 2,145 primary clinical specimens testing positive for M. genitalium 16S rRNA by transcription-mediated amplification (TMA) were initially titered by the same assay using serial 10-fold dilutions to determine relative target nucleic acid burden. Specimens were then processed for MRM-LDT. Findings were stratified by men who have sex with men (MSM; n = 3 settings), community care (n = 2), and university student (n = 3) populations. The mean log10 target nucleic acid titer of a TMA-positive specimen was 3.46 (median 3; range 0–10). A 43.2% MRM-LDT detection rate was found in specimens derived from community care settings. Analogous assessments of university student and MSM demographics revealed 60.8% and 62.0% detection, respectively (P ≤ 0.0004 versus community care). Within the university student demographic, differences existed in target nucleic acid titer for two settings (P = 0.01); similar differences were encountered between a local MSM cohort and two that were nationally based (P ≤ 0.01). Within the university cohort, MRM-LDT detection rate was increased in symptomatic patients (P = 0.005). M. genitalium macrolide resistance rates among multiple demographics, as determined by MRM-LDT, are high in the United States and are consistent with target nucleic acid burden within the primary specimen. However, caveats experienced within subgroupings of these demographics support reflex MRM-LDT on M. genitalium-positive specimens.IMPORTANCEData generated from a high-throughput, automated system and presented in this report expand upon knowledge of Mycoplasma genitalium-specific macrolide resistance in the United States and may further inform providers on population- or demographic-based considerations for macrolide resistance mutation determination in M. genitalium.